Review of the evidence on noise exposure and non-auditory health effects in the european network for noise and health (ENNAH) - Hansell, A; Floud, S; Laslo, H; Jarup, L (2010)
The two year European Network for Noise and Health (ENNAH) project launched in September 2009, with the aims of establishing a network of experts on noise and health in Europe and informing future research directions and policy needs in Europe. A key component of the project is a literature review to (i) consolidate the existing state of the art knowledge on noise exposure and non-auditory health effects, (ii) to identify gaps in the evidence and (iii) to suggest the future research needs and hypotheses to be tested. A workshop following on from the launch meeting was used to identify existing literature and structure the literature review with input from experts in noise and health from over Europe who were part of the network and from invited speakers. Key areas covered were • Refinement of review objectives • How to deal with grey literature • Identification of current reviews • Gaps e.g. joint effects of noise and air pollution - do they interact or are they confounders of each other? • Resources This paper will present the on-going work of the literature review and the presentation will be used to invite comments from the audience to help identify important reviews and topic areas that have not been covered to date.